THE PROBLEM OF USING OPEN EDUCATIONAL RESOURCES IN THE LITHUANIAN LANGUAGE AS A LESS WIDESPREAD LANGUAGE IN THE WORLD - Zuzevičiūtė, Vaiva; Ruibytė, Laima; Adamonienė, Rūta; Stepanovienė, Aušra; Pranevičienė, Birutė; Dobržinskienė, Rasa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The demand to promote development of Open Educational Resources (OER) in less used languages is relevant all across Europe. Although numerous education resources are available today, their access in the Lithuanian language is very scarce. The aim of the article is to reveal the importance of OER in the Lithuanian language for the development of teachers’ competences. This is crucial to assure the quality of teaching material by providing a possibility to disseminate innovations, to develop creativity and consistency as well as to share created teaching resources. The article is based on scientific literature analysis and descriptive methods. OER in Lithuanian are crucial to assuring the quality of teaching material by providing teachers a possibility to develop their competences, creativity, and consistency as well as to apply innovations and share the designed resources of teaching.